How the global threat of pests and diseases impacts plants, people, and the planet. Issue 1 (18th December 2019) - Spence, Nicola; Hill, Louise; Morris, Jake
Societal Impact Statement: Plants provide us with the building blocks of life—oxygen, food, fuel, clean air, and water and a stable environment. And yet, in the modern world, they are under ever‐increasing threat from introduced pests and diseases. Such epidemics can have devastating impacts on human health, biodiversity, and food security, as well as contributing to environmental change. The Chief Plant Health Officer at Defra has a key role in the development of policy to protect the UK's plants from biosecurity risks, and we explore the different approaches being taken to manage these risks and protect the UK's plants for the future. Summary: Plants have an essential role in addressing the great social and environmental challenges of our time. However, the risk from invasive plant pests and pathogens is also significant and constantly growing as a result of increasing globalization and environmental change. The UK's plant health regime aims to manage that risk to protect the enormous value of plants and trees; from the value of crops and forestry products, to ecosystem services and societal benefits. We discuss the role of the Chief Plant Health Officer at Defra in advising Ministers on plant health policy, including through dialogue with stakeholders and the research community. Case studies demonstrate how plant health threats can put at risk human physical and mental health, the economic benefits of healthy plants, and food security. We discuss the UK's risk‐based approach to protecting the UK's plant resource, and the approaches being taken to manage different kinds of risks, including import controls, management of threats once established, breeding resistant varieties, utilizing citizen science, and awareness raising. Abstract : Plants provide us with the building blocks of life—oxygen, food, fuel, clean air, and water and a stable environment. And yet, in the modern world, they are under ever‐increasing threat from introduced pests and diseases. Such epidemics can have devastating impacts on human health, biodiversity, and food security, as well as contributing to environmental change. The Chief Plant Health Officer at Defra has a key role in the development of policy to protect the UK's plants from biosecurity risks, and we explore the different approaches being taken to manage these risks and protect the UK's plants for the future.